Physical and Proximate Analysis of Instant Vegan Baby Complementary Foods by Freeze Drying Method - Anindya Niken Samsudar; Fitriyono Ayustaningwarno; Lilis Wijayanti (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
The 2023 SKI data shows that conventional complementary feeding is still inappropriate for the 6-11 month age group. Foods high in sugar still make up a large part of commercial complementary foods. The purpose of this study was to determine the effects of cold-processed vegan instant complementary foods made from local ingredients, including various types of tomatoes, mushrooms, and seaweed, on infants aged 9-11 months. The study utilized experimental methods with physical test parameters such as water solubility, water absorption, viscosity, and color, as well as proximate tests such as fat content, protein content, water content, ash content, carbohydrate content, and total calories. The research was conducted with one sampling and three tests. The addition of tomatoes, mushrooms, and nori had a significant effect (p<0.050) on protein content (p=0.027), carbohydrate content (p=0.001), total calories (p=0.000), absorbency (p=0.030), viscosity (p=0.000), and color a* (p=0.003) and color b* (p=0.050). The addition of tomato, mushroom, and nori did not have a significant effect (p>0.005) on fat content (p=0.066), ash content (p=0.051), water content (p=0.301), solubility (p=0.107), and L* color (p=0.422). The addition of tomatoes, mushrooms, and seaweed to instant vegan complementary foods has a significant effect on the following parameters: protein content, carbohydrate content, total calories, water absorption, viscosity, and color a* and color b*. The addition of tomatoes, mushrooms, and seaweed to instant vegan complementary foods did not have a significant effect on the following parameters: fat content, ash content, water content, solubility, and L* color.